Biodegradation of PP and PE blended with PHBV in soil samples - Gonçalves, Suely Patricia Costa [UNESP]; Franchetti, Sandra Mara Martins [UNESP] (Wiley-Blackwell, 2015)
This work studied the biodegradation of polyethylene/poly(hydroxybutyrate-co-hydroxyvalerate) (PE/PHBV) and polypropylene/PHBV (PP/PHBV) films, by respirometry in soil, using biometric flasks. Additionally, the characteristics of the soil were measured by pH, moisture, organic matter content, and quantification of microorganisms. The soil analysis showed that the two blends inhibited the soil bacteria activity and stimulated the growth of fungi. The PE/PHBV (80/20) blend is more susceptible to the microbial action in the soil than the PP/PHBV (80/20) blend. The blends showed higher biodegradation in the PHBV amorphous phase, due to consumption of ester groups, leading to rearrangement of the crystalline phase of PHBV fraction. On the basis of quantification of CO2, the PE/PHBV (80/20) film showed approximately 7% biodegradation, and the beginning occurred in a period of 60 days. Moreover, the employed methods Fourier transform infrared spectroscopy and X-ray diffraction completed the information obtained by the respirometry method, showing evident changes in the polymer chains structure and crystallinity, respectively.
Keywords: Blends; FT-IR; X-ray; Respirometry; Soil